2001
DOI: 10.1292/jvms.63.637
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of in vitro and in vivo Antiviral Activity of Lactoferrin and Ribavirin upon Hantavirus.

Abstract: ABSTRACT. Mechanisms of anti-hantaviral activities of bovine lactoferrin (LF) and ribavirin (Rbv) were investigated. Hantavirus focus formation at 48 hr was 15% of the control in cells treated with 400 µg/ml LF for 1 hr at 37°C prior to viral infection. Post infection treatment with 100 µg/ml Rbv also inhibited the focus formation to 2.5% of the control. Combined LF pre-and Rbv post-infection treatment completely inhibited focus formation. Viral glycoprotein (G2) and nucleocapsid protein (NP) syntheses were de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 40 publications
2
36
0
1
Order By: Relevance
“…These results suggested that the mRNA produced from cRNA templates was defective, perhaps in its ability to be translated. These findings are similar to those reported by Murphy et al, who showed that ribavirin inhibits the synthesis of viral proteins and RNA and viral shedding of another hantavirus, Seoul virus, strain SR-11 (16). However, the mechanism of inhibition was not elucidated.…”
Section: Discussionsupporting
confidence: 90%
“…These results suggested that the mRNA produced from cRNA templates was defective, perhaps in its ability to be translated. These findings are similar to those reported by Murphy et al, who showed that ribavirin inhibits the synthesis of viral proteins and RNA and viral shedding of another hantavirus, Seoul virus, strain SR-11 (16). However, the mechanism of inhibition was not elucidated.…”
Section: Discussionsupporting
confidence: 90%
“…It is considered to be a bioactive milk protein that plays versatile roles in the immune system responses and helps to protect the body from various infections. 5,6) Many studies have already demonstrated that bovine lactoferrin (bLF) features a variety of bioactivities such as anti-bacterial, [6][7][8][9] antiviral, [10][11][12] anti-oxidative, 13) anti-tumor, [14][15][16] anti-inflammatory, [17][18][19][20] immunomodulatory, 21) analgesic 22) and antistress 23) effects. Recently, it has also been reported that oral administration of bLF to patients suffering chronic hepatitis C reduced the amount of hepatitis C virus.…”
mentioning
confidence: 99%
“…This combination therapy also demonstrated significantly increased survival rates in an in vivo mice model, not particularly surprising as lactoferrin inhibits viral adsorption to cells and Ribavirin interferes with viral RNA synthesis [122]. Moreover, the antiviral synergy of lactoferrin/lactoferricin with Cidofovir, Ribavirin, Zidovudine, and Acyclovir as all been well documented against human cytomegalovirus, hepatitis C virus, human immunodeficiency virus 1 and herpes simplex virus, respectively [13,[174][175][176].…”
Section: Synergy Between Milk Proteins and Conventional Antiviral Drugsmentioning
confidence: 81%
“…Binding to virus particle and cellular receptor on target cell [74] Hantavirus lactoferrin Binding to cellular molecules; synergistic effect with Ribavirin on inhibiting viral replication [72,122] Vesicular stomatitis virus lactoferrin Induction interferon-/ expression to inhibit viral replication [11] Friend virus complex human lactoferrin Regulation on the myelopoiesis; synergistic effect with interferon- [11,56,57,64] Human papillomavirus human and bovine lactoferrin, human and bovine lactoferricin…”
Section: Hepatitis B Virus Iron-or Zinc-saturated Lactoferrinmentioning
confidence: 99%
See 1 more Smart Citation